TEACHERS’ EFFORTS TO IMPROVE ENGLISH UNDERSTANDING THROUGH PARTICIPATORY LEARNING IN SIXTH-GRADE STUDENTS AT SDN 066053 - Nadira Fathia Siregar; Elbert Gusmiarni Gea; Azzirah Amanda; Seprianytami Siregar (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to analyze teachers’ efforts to enhance sixth-grade students’ English understanding through participatory learning at SDN 066053. Employing a qualitative descriptive approach, data were collected through classroom observations, interviews with English teachers, and documentation related to learning activities. The findings show that teachers apply several participatory strategies, including group discussions, interactive games, project-based tasks, and peer collaboration to increase student engagement and comprehension. These strategies create an active learning environment where students are encouraged to express ideas, ask questions, and work collaboratively. The study concludes that participatory learning significantly supports students’ English understanding, particularly in vocabulary mastery, sentence formation, and simple communication skills. The research suggests that continuous training and reflective practice are essential for teachers to optimize participatory learning in English instruction